Validation of Hypertensive Disorders During Pregnancy: ICD-10 Codes in a High-burden Southeastern United States Hospital. Issue 4 (4th March 2021) - Labgold, Katie; Stanhope, Kaitlyn K.; Joseph, Naima T.; Platner, Marissa; Jamieson, Denise J.; Boulet, Sheree L.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Identification of hypertensive disorders in pregnancy research often uses hospital International Classification of Diseases v. 10 (ICD-10) codes meant for billing purposes, which may introduce misclassification error relative to medical records. We estimated the validity of ICD-10 codes for hypertensive disorders during pregnancy overall and by subdiagnosis, compared with medical record diagnosis, in a Southeastern United States high disease burden hospital. Methods: We linked medical record data with hospital discharge records for deliveries between 1 July 2016, and 30 June 2018, in an Atlanta, Georgia, public hospital. For any hypertensive disorder (with and without unspecified codes) and each subdiagnosis (hemolysis, elevated liver enzymes, and low platelet count [HELLP] syndrome, eclampsia, preeclampsia with and without severe features, chronic hypertension, superimposed preeclampsia, and gestational hypertension), we calculated positive predictive value (PPV), negative predictive value (NPV) sensitivity, and specificity for ICD-10 codes compared with medical record diagnoses (gold standard). Results: Thirty-seven percent of 3, 654 eligible pregnancies had a clinical diagnosis of any hypertensive disorder during pregnancy. Overall, ICD-10 codes identified medical record diagnoses well (PPV, NPV, specificity >90%; sensitivity >80%). PPV, NPV, and specificity were high for all subindicators (>80%). Sensitivity estimates were high for superimposed preeclampsia, chronic hypertension, and gestational hypertension (>80%); moderate for eclampsia (66.7%; 95% confidence interval [CI] = 22.3%, 95.7%), HELLP (75.0%; 95% CI = 50.9%, 91.3%), and preeclampsia with severe features (58.3%; 95% CI = 52.6%, 63.8%); and low for preeclampsia without severe features (3.2%; 95% CI, 1.4%, 6.2%). Conclusions: We provide bias parameters for future US-based studies of hypertensive outcomes during pregnancy in high-burden populations using hospital ICD-10 codes.